Application Of Azadirachta Indica Leaves As Natural Coagulant For Kitchen Wastewater Treatment - Saleh, Nor Liyana (Universiti Sains Malaysia, 2021)
One of the alternative methods for treating wastewater effluent is by coagulation-flocculation treatment. The conventional coagulants used in this process, on the other hand, may have a negative impact on the environment because they are primarily chemical-based and not environmentally friendly. As a result, producing an environmentally friendly coagulant is required to achieve sustainable development. Previous research conducted did not further discussed about the use of extracts from Azadirachta indica (neem) leaves as a coagulant to reduce other parameters except for turbidity. The ability of neem leaves powder, neem leaves treated with distilled water and hydrochloric acid (AI-powder, AIp-DW, AIp-0.1M HCl and AIp-0.025M HCl), to act as a coagulant in this study was evaluated using domestic wastewater using jar test. The coagulation activity and removal efficiency (RE) of turbidity, colour, oil and grease and chemical oxygen demand (COD) were calculated from jar test results. The pH level of wastewater was controlled at pH 7 to increase its efficiency during jar test. AIp-0.1M HCl recorded the highest RE for all parameters, which are 58%, 44% and 6.44% of turbidity, colour and oil and grease, respectively. However, the COD value recorded was increasing for all types of coagulant used in this project due to the remaining organic matter in neem leaf powder has not been removed. From the result, the use of extracts from A. indica leaves as coagulants has a potential to be proposed as an alternative coagulant in the treatment of wastewater not only from domestic sources but also from industrial sources via coagulation-flocculation.